Upaya Peningkatan Kepedulian Masyarakat Tentang Bahaya Mikroplastik Pada Masyarakat di Pesisir Pantai Padang - Radian Ilmaskal; Nizwardi Azka; Dian Paramitha Asyari; Fadhilatul Hasnah (STIKes Alifah Padang, 2023)
Plastic waste continues to be a problem in many countries around the world. The use of plastic is very common in various types of products. Padang Beach is one of the main tourist destinations in Padang City, but until now there was still a lot of scattered garbage, especially after the rain. The purpose of this activity is to increase the understanding and awareness of coastal communities and the younger generation of the negative impact of microplastics and contribute to cleaning up trash on Padang Beach. The activity methods are participatory counseling and gotong royong. Activities were carried out in January 2023. Participants involved were coastal communities, students, teenagers, and the general public, who were recruited online through social media. The coastal community welcomed this activity and actively participated. There was a significant increase in community knowledge (9%) and attitude (10%) about the dangers of microplastics. It is expected that visitors and beach vendors will be aware of beach cleanliness and refrain from littering. The government is expected to provide waste disposal sites in nearby locations.